The Micronemal Plasmodium Proteins P36 and P52 Act in Concert to Establish the Replication-Permissive Compartment Within Infected Hepatocytes - Arredondo, Silvia A.; Swearingen, Kristian E.; Martinson, Thomas; Steel, Ryan; Dankwa, Dorender A.; Harupa, Anke; Camargo, Nelly; Betz, William; Vigdorovich, Vladimir; Oliver, Brian G.; Kangwanrangsan, Niwat; Ishino, Tomoko; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Within the liver, Plasmodium sporozoites traverse cells searching for a “suitable” hepatocyte, invading these cells through a process that results in the formation of a parasitophorous vacuole (PV), within which the parasite undergoes intracellular replication as a liver stage. It was previously established that two members of the Plasmodium s48/45 protein family, P36 and P52, are essential for productive invasion of host hepatocytes by sporozoites as their simultaneous deletion results in growth-arrested parasites that lack a PV. Recent studies point towards a pathway of entry possibly involving the interaction of P36 with hepatocyte receptors EphA2, CD81 and SR-B1. However, the relationship between P36 and P52 during sporozoite invasion remains unknown. Here we show that parasites with a single P52 or P36 gene deletion each lack a PV after hepatocyte invasion, thereby pheno-copying the lack of a PV observed for the P52/P36 dual gene deletion parasite line. This indicates that both proteins are equally important in the establishment of a PV and act in the same pathway. We created a Plasmodium yoelii P36mCherry tagged parasite line that allowed us to visualize the subcellular localization of P36 and found that it partially co-localizes with P52 in the sporozoite secretory microneme organelles. Furthermore, through co-immunoprecipitation studies in vivo, we determined that P36 and P52 form a protein complex in sporozoites, indicating a concerted function for both proteins within the PV formation pathway. However, upon sporozoite stimulation, only P36 was released as a secreted protein while P52 was not. Our results support a model in which the putatively glycophosphatidylinositol (GPI)-anchored P52 may serve as a scaffold to facilitate the interaction of secreted P36 with the host cell during sporozoite invasion of hepatocytes.